2015
DOI: 10.7314/apjcp.2015.16.1.239
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Exposure to Pesticides and Occurrence of Acute Leukemia in Iran

Abstract: Background: One of the causes of acute leukemia can be exposure to certain chemicals such as pesticides. This study determined the relationship between exposure to pesticides and the occurrence of acute leukemia in Fars province, south of Iran. Materials and Methods: Between April 2011 and April 2013 in a case-control study conducted in Nemazee Hospital in Shiraz, Southern Iran; 314 subjects diagnosed with acute leukemia (94 pediatric cases and 220 adults) were enrolled to determine any correlation between exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The high‐intensity use of organophosphate (OP) pesticides has contributed to morbidity and mortality in farmworkers and their families through acute or chronic pesticide‐related illnesses . Recently, the long‐term effects of pesticide exposure have been associated with many diseases . The Phytoner study reported an association between chronic exposure to pesticides and cognitive impairment .…”
Section: Introductionmentioning
confidence: 99%
“…The high‐intensity use of organophosphate (OP) pesticides has contributed to morbidity and mortality in farmworkers and their families through acute or chronic pesticide‐related illnesses . Recently, the long‐term effects of pesticide exposure have been associated with many diseases . The Phytoner study reported an association between chronic exposure to pesticides and cognitive impairment .…”
Section: Introductionmentioning
confidence: 99%
“…The data according to the Food and Agriculture Organization of the United Nations (FAO) showed that the average use of pesticides per area of cropland (kg/ha) in each year in mainland China increased from 1990 to 2015. Pesticide exposure is a known risk factor of many diseases, such as cancer [814], asthma [15, 16], diabetes [1719], Parkinson’s disease [2022], leukemia [23, 24], mental diseases [2528], and non-Hodgkin lymphoma [29] and may also be related to sleep disturbances. A case-control design study showed that increased tension, greater depression and fatigue, and more frequent symptoms of central nervous system disturbances were observed in pesticide-exposed women [30].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of leukemia in men was nearly twice as much as women (6.82 vs. 3.49 per 100,000). The main reason was that men were more exposed to risk factors such as; smoking and occupational and environmental hazards like chemical agents, pesticides and radiation [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%